Millipede and centipede (Myriapoda: Diplopoda, Chilopoda) assemblages in secondary succession: variance and abundance in Western German beech and coniferous forests as compared to fallow ground - A. Schreiner; P. Decker; K. Hannig; A. Schwerk (Web Ecology, 2012)
Successional processes are an important element of commercial-forest ecosystems. They can be followed by studying the species composition of various animal groups, e.g. millipedes. Over the vegetation periods 2009 and 2010, we pitfall-trapped millipedes and centipedes (Myriapoda: Diplopoda, Chilopoda) on 21 Western German (North Rhine-Westphalian) deciduous and coniferous forest as well as fallow-ground sites of increasing age (1–165 yr) and determined them to the species and sex. Diplopoda (2009: 1659/2010: 3417 individuals) outnumbered the trapped Chilopoda (2009: 37/2010: 111 individuals) by far while the general catching results approximately doubled from 2009 to 2010. Indirect gradient analysis (CA) revealed that the influence of the habitat type on the formation of diplopod assemblages exceeded the influence of the successional stage. Although no clear trend in individual-count development over time occurred in most species detected, Julus scandinavius (Latzel, 1884) significantly increased in numbers with ageing of the deciduous (beech) forests. In conclusion, J. scandinavius may be a suitable bioindicator of deciduous-forest succession. More data are necessary to transfer our results into a mathematical function describing the course of increasing J. scandinavius abundance.